Strategi Pemasaran Produk Takafulink Salam dalam Meningkatkan Jumlah Nasabah - Fazrianti, Nurul (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Sharia insurance is an effort to protect and help each other among policyholders (participants) which is carried out through the collection and management of tabarru funds that provide a pattern of return to face certain risks through contracts that are in accordance with sharia principles. Insurance is a way to minimize the occurrence of greater risks, which may be experienced by everyone. In the present day there are more and more other sharia insurance companies that require every sharia insurance company to continue to improve existing marketing strategies in order to achieve their goals with increasing customers in the midst of competition in the sharia insurance business. Similarly, Takafulink Salam's product marketing strategy must continue to be improved its marketing strategy to increase the number and interest of customers in Takafulink Salam products. The purpose of this study is to find out the marketing strategies carried out can increase the number and interest of customers. The research method used is descriptive qualitative by conducting research into the field as well as providing an overview of the marketing strategy carried out by agents in increasing the number of customers. The results of the research stated that the marketing strategy carried out was not enough to help increase the number and interest of customers in the Takafulink Salam insurance product. It is still necessary to continue to improve other strategies in order to increase the number and interest of customers in the Takafulink Salam insurance product.